2022
DOI: 10.1155/2022/4262094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gut Microbiota in Patients with Exacerbated Symptoms of Schizophrenia following Therapy with Amisulpride: A Pilot Study

Abstract: Evidence is mounting that the gut microbiome is related to the underlying pathogenesis of schizophrenia. However, effects of amisulpride on gut microbiota are poorly defined. This study was aimed at analyzing cytokines and fecal microbiota in patients with exacerbated symptoms of schizophrenia treated with amisulpride during four weeks of their hospital stay. In the present study, feces collected from patients with schizophrenia were analyzed using 16S rRNA pyrosequencing and bioinformatic analyses to ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A total of 19 studies met the inclusion criteria (see PRISMA flowchart, Figure 1). Of these, 14 were longitudinal studies that reported data on pre-and post treatment differences in gut microbiome across 484 patients treated with either antidepressants (six studies [21][22][23][24][25][26]; N=167) or antipsychotics (eight studies [27][28][29][30][31][32][33][34]; N=317); Five studies reported cross-sectional data on gut microbiome features in patients treated with antipsychotics (N=182) vs antipsychotic-free patients (N=165) [27,[35][36][37][38] and two on patients treated with antidepressants vs antidepressants-free patients [26,38,39]. No studies directly investigated mood stabilizers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 19 studies met the inclusion criteria (see PRISMA flowchart, Figure 1). Of these, 14 were longitudinal studies that reported data on pre-and post treatment differences in gut microbiome across 484 patients treated with either antidepressants (six studies [21][22][23][24][25][26]; N=167) or antipsychotics (eight studies [27][28][29][30][31][32][33][34]; N=317); Five studies reported cross-sectional data on gut microbiome features in patients treated with antipsychotics (N=182) vs antipsychotic-free patients (N=165) [27,[35][36][37][38] and two on patients treated with antidepressants vs antidepressants-free patients [26,38,39]. No studies directly investigated mood stabilizers.…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal studies Of the eight longitudinal studies involving antipsychotics, three investigated Risperidone [27,31,32], one Amisulpiride [33], one Olanzapine [30], two Quetiapine [28,29], and one a variety of different antipsychotics [34]. Five studies reported data on gut microbiome alpha diversity before and after treatment with antipsychotics [28,30,32,33,38]. All studies reported the Shannon index as a measure of alpha diversity.…”
Section: Antipsychoticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a pilot study, Zheng et al [49] aimed to analyze the consequences of amisulpride (400-1200 mg/kg) treatment for four weeks by applying biochemical and molecular biology protocols. As observed in the case of all atypical antipsychotics (AAP), it caused an increase in the levels of the short-chain fatty acid (SCFAs)-producing bacteria Dorea and Butyricicoccus and of those that are potentially pathogenic, such as Actinomyces and Porphyromonas with persistence at a high ratio of Desulfovibrio.…”
Section: Amisulpridementioning
confidence: 99%